Measurement of inflight shell areal density near peak velocity using a self backlighting technique. (May 2016) - Pickworth, L A; Hammel, B A; Smalyuk, V A; MacPhee, A G; Scott, H A; Robey, H F; Landen, O L; Barrios, M A; Regan, S P; Schneider, M B; Jr, M Hoppe; Kohut, T; et al.
Abstract: The growth of perturbations in inertial confinement fusion (ICF) capsules can lead to significant variation of inflight shell areal density (ρR), ultimately resulting in poor compression and ablator material mixing into the hotspot. As the capsule is accelerated inward, the perturbation growth results from the initial shock-transit through the shell and then amplification by Rayleigh-Taylor as the shell accelerates inwards. Measurements of ρR perturbations near peak implosion velocity (PV) are essential to our understanding of ICF implosions because they reflect the integrity of the capsule, after the inward acceleration growth is complete, of the actual shell perturbations including native capsule surface roughness and "isolated defects". Quantitative measurements of shell-ρR perturbations in capsules near PV are challenging, requiring a new method with which to radiograph the shell. An innovative method, utilized in this paper, is to use the self-emission from the hotspot to "self- backlight" the shell inflight. However, with nominal capsule fills there is insufficient self-emission for this method until the capsule nears peak compression (PC). We produce a sufficiently bright continuum self-emission backlighter through the addition of a high-Z gas (∼ 1% Ar) to the capsule fill. This provides a significant (∼10x) increase in emission at hυ∼8 keV over nominal fills. "Self backlit" radiographs are obtained for times when the shock is rebounding from the capsule center, expanding out to meet the incoming shell, providing a means to sample the capsule optical density though only one side, as it converges through PV.